Physical properties of neoprene based solvent adhesive blended with TAPE - Alfeche, Lalaine Joan V.; Tumolva, Terence P. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The possibility of incorporating a bio-based adhesive in a commercial solvent adhesive was investigated to potentially reduce the adhesive's solvent and synthetic resin content. Different amounts of TAPE (tannic acid-polyethylene glycol), a bioadhesive, were added to a neoprene (polychloroprene) based solvent adhesive (NPA) as a filler and tested for its influence. Blends were prepared through physical mixing in 3:1, 2:1 and 1:1 of NPA to TAPE ratio. The effect of addition of TAPE was tested through measuring the adhesion performance by means of peel strength. The blends were applied in non-abraded and abraded surfaces of aluminum metal sheets with bonded joints cured at room temperature and 90°C. Its performance when exposed to moisture was also determined. The blends were also characterized using FTIR, DSC and SEM. Analysis of Variance (ANOVA) was conducted to check statistical significance among the parameters. Addition of TAPE in 2:1 and 3:1 blends showed an increase of 43-58% in peel strength (room temperature cured; non-abraded substrates). TAPE blends in abraded substrates generally showed inferior performance due to impurities and stress concentration at the voids of the interface. Most of the adhesives were less resistant to moisture due to the plasticizing and displacing effect of water. Heat curing the 3:1 non-abraded joints showed to be 22% and 15% better compared to the commercial adhesive in dry and wet conditions respectively. FTIR spectra suggested that physical interaction occurs between NPA and TAPE due to the absence of new absorbance peaks. DSC showed that the blends formed are compatible due to a single glass transition temperature (Tg) observed. SEM showed that addition of TAPE blends causes changes in morphology with varying degree of microphase aggregation. Adhesion mechanism was primarily due to physical adhesion from secondary forces of attraction. ANOVA showed that the NPA-TAPE blend ratio is statistically significant to peel strength.
Thesis (Master of Science in Chemical Engineering)--University of the Philippines Diliman
Keywords: Adhesives